Implementation Of Augmented Reality Procedures For Prayer Using Marker-Based Tracking Method - Adi Darmanto; Faisal Reza Pradhana; Dihin Muriyatmoko; Oddy Virgantara Putra; Lukman Effendi (Procedia of Engineering and Life Science, 2021)
Prayer learning activities at PAS Baitul Qur'an Ponorogo Kindergarten have so far been carried out with face-to-face practice between teachers and students. However, the teachers teach the proper way of praying during the pandemic. This study aims to introduce Augmented Reality (AR) technology to teachers and children as a medium for learning to pray. From this research resulted in the application "Let's Learn Prayer" which contains guidance on how to pray and pray in the form of three-dimensional animation. In addition, this application is equipped with a card (marker) that represents each prayer movement. The animation of the prayer can move when the user does the marking. As a result, animations can appear on the smartphone screen. This application development stage uses Waterfall model steps and marker-based tracking. The use of AR applications for prayer learning can increase students' interest and understanding in implementing prayer movements